Food quality assurance : - Alli, Inteaz (CRC Press, 2004)
The field of food quality assurance has evolved substantially over the past decade, and certain key developments have become widely accepted. These include Quality Systems (e.g., ISO 9000) and HACCP. Consequently, it has become essential for undergraduate Food Science and Food Technology students preparing for careers in the food industry to have some basic training in these systems as part of the curricula in their university or college programs. Food Quality Assurance: Principles and Practices integrates the latest principles, practices, and terminology of food safety systems with those of quality management systems to provide an understanding of a single food quality management system. Chapters define industry terminology, review the differences and components of food quality and food safety, explain Quality Programs and Quality Systems, and thoroughly examine Good Manufacturing Practices and HACCP. Written primarily as an undergraduate-level text for Food Quality Assurance and Food Quality Management courses, the book combines the fundamentals of food safety and quality systems with the latest data from recognized international and national organizations. This is an essential guide for teaching food quality assurance to students.